Building Customer Satisfaction and Loyalty By Increasing Service Innovation and Service Quality On Iot Control Center Customers - Prasetyo, Iwan; Wahyuningtyas, Ratri (Journal of Business and Management Review, 2024)
Research Aims: This study aims to examine the influence of service innovation and service quality on customer satisfaction at Telkomsel IOT Control Center and its impact on customer loyalty. Design/methodology/approach: This study is a quantitative research conducted using a sample of 200 accounts from the IOT control center. Data collection was carried out through questionnaire distribution. Data analysis was performed using the Structural Equation Modeling (SEM) technique, specifically Partial Least Squares (PLS). Research Findings: Findings of this research is that customer loyalty of Telkomsel IOT control center can be built through increasing customer satisfaction, which is formed by good service innovation and satisfying service quality. Therefore, in efforts to enhance customer loyalty, Telkomsel should create many service innovations and focus on service quality that can satisfy customers. Theoretical Contribution/Originality: In the effort to build customer loyalty, the development of service innovation and improvement of service quality need to be focused on customer satisfaction Keywords: customer loyalty, customer satisfaction, service innovation, service quality, IOT control center